Pembuatan Trikalsium Fosfat Berpori Menggunakan Metode Protein Foaming -Starch Consolidation Dengan Variasi Rasio Bahan Baku Dalam Slurry Dan Temperatur Pengeringan - Wan Elsa Novtari Adiani; Ahmad Fadli; Irdoni Irdoni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Porous tricalcium phospate has been widely used in the implantation of bone tissue. Protein foaming-consolidation method is a technique for production of porous tricalcium phosphate using egg white as pore creating agent. The purpose of this research was to investigate variation of the ratio of egg white in slurry and drying temperature effects on physical, and chemical of porous TCP by using protein foaming-consolidation method. This research was started by mixing 7 grams of TCP powder, 2 grams of starch, 1,5 grams Darvan 821A, with 5 grams of egg white, 7 grams of egg white and 9 grams of egg white. The slurries were stirred at 150 rpm for 3 hours. Then, the slurries were cast in a cylindrical stainless steel mold and heated at 180°C, 200°C, and 220°C for 1 hour. Subsequently, dried samples were demolded. Next, samples were burned at 600°C for an hour. For the final steps, samples were sintered at 1100°C for 2 hours. Number of egg white and drying temperature increased result in porosity increased and compressive strength of porous tricalcium phospate decreased. This research resulted in porous TCP with 67,6%-78,13% porosity and the compressive strength was 0,14-1,4 MPa.Keyword : compressive strength, egg white, porosity, tricalcium phosphate